Our experiences in the treatment of peripheral primitive neuroectodermal tumour in the years 2000-2010 in the Cancer Centre in Hradec Králové - Kopecký, Jindřich; Kopecký, Otakar; Priester, Peter; Petera, Jiří; Slováček, Ladislav (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Peripheral primitive neuroectodermal tumour (pPNET) is typical for childhood and adolescent age. This kind of tumour belongs to the tumour family of Ewing sarcoma. The primitive neuroectodermal tumour is mainly localized in the central nervous system; less frequently it may also occur peripherally. The incidence of generalized peripheral primitive neuroectodermal tumour in adults is rare according to the available literature and treatment modalities are limited. The therapy is derived from protocols which were developed for the treatment of children. Material and methods : Patients with peripheral primitive neuroectodermal tumours were retrospectively evaluated according to therapeutic response and overall survival. Results : From January 2000 to December 2010 eleven patients were diagnosed with peripheral primitive neuroectodermal tumour in the Cancer Centre in Hradec Králové, where eight of them were also treated. The median of age at the time of diagnosis was 45 years. The median overall survival was 571 days. The most commonly used cytotoxic agents were ifosfamide, doxorubicin and etoposide. Conclusions : The results of treatment in patients with peripheral primitive neuroectodermal tumour are not encouraging, despite a multimodal therapeutic approach involving chemotherapy, radiotherapy and surgical treatment. It is therefore necessary to centralize patients in cancer centres and to offer them preferably participation in clinical trials.